Water supply of the Topkap? Palace kitchen complex: Review and interpretation based on new findings - Engudar, Ece Uysal; Yergun, Uzay (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
Topkapi Palace's kitchen complex consists of the cooking units (kitchens), dorms, masjids, baths, storages, storerooms and cellars and is where the outer services (Birun) served the inner ones (Enderun). These units required water for drinking, cooking, cleaning and watering purposes. The water was supplied from Halkali and Kirkcesme. Water towers and wells then transmitted that to the kitchens' fountains, alongside baths, ablutions and restrooms. If the Halkali and Kirkcesme water were insufficient, water from the city of Terkos was delivered to the palace, as well. Channels disposed of wastewater into the Marmara Sea. It has been determined that the findings obtained in the literature review do not review a holistic view of the whole study area. In order to fill the gaps, the new documents were provided from the Ottoman Archives of the Turkish Republic Presidency State Archives, archives from the Institute of Ekrem Hakki Ayverdi, the National Library of France, and The Harvard Map Collection. To prove the accuracy of some of the new documents and to establish spatial relations, surface research and excavations are required within the study area. The aim of this article is to try to search for a context for the whole water supply of the palace kitchens by evaluating all available resources, spatial functions and connections.
Keywords: Disposing of wastewater; fountains; Topkap? Palace kitchen complex; water supply; water wheel of well; Architecture